2015
DOI: 10.1016/j.matdes.2015.06.140
|View full text |Cite
|
Sign up to set email alerts
|

Development of Al–Mn–Mg 3004 alloy for applications at elevated temperature via dispersoid strengthening

Abstract: In this study, the potential applications of Al-Mn-Mg 3004 alloy at elevated temperature have been evaluated through the systematic study of the precipitation behavior of α-Al(MnFe)Si dispersoids and their effect on material properties during precipitation treatment and long-term thermal holding. The results demonstrate a significant dispersion strengthening effect caused by the precipitation of fine uniformly distributed dispersoids during precipitation treatment. The peak compression yield strength (YS) at 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
113
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(119 citation statements)
references
References 36 publications
6
113
0
Order By: Relevance
“…A trace of Cu was detected in the dispersoids in the Cu containing alloys by TEM-EDS analysis. All dispersoids are identified as α-Al(Mn,Fe)Si according to the results of TEM-EDS and literature [1][2][3]5,6]. The equivalent diameter of the dispersoids in the base alloy (DU0) is 47 nm, whereas the diameters of the dispersoids in the Cu containing alloys are between 32 and 37 nm (Figure 7a), which is smaller than that in the base alloy.…”
Section: The Influence Of Cu On Dispersoid Features and Thermal Stabimentioning
confidence: 87%
See 3 more Smart Citations
“…A trace of Cu was detected in the dispersoids in the Cu containing alloys by TEM-EDS analysis. All dispersoids are identified as α-Al(Mn,Fe)Si according to the results of TEM-EDS and literature [1][2][3]5,6]. The equivalent diameter of the dispersoids in the base alloy (DU0) is 47 nm, whereas the diameters of the dispersoids in the Cu containing alloys are between 32 and 37 nm (Figure 7a), which is smaller than that in the base alloy.…”
Section: The Influence Of Cu On Dispersoid Features and Thermal Stabimentioning
confidence: 87%
“…In the base alloy (DU0, Cu-free), two types of intermetallic particles were observed (Figure 2a). The grey particles correspond to the Al 6 (Mn,Fe) intermetallic phase and the black ones are primary Mg 2 Si [6,9,13]; both are intermetalllics distributed in the interdendrite regions. In the Cu containing alloys, the grey particles are Al 6 (Mn,Fe) intermetallic, in which a small amount of Cu can be detected.…”
Section: Influence Of Cu On Intermetallic Phases and Dispersoid Distrmentioning
confidence: 99%
See 2 more Smart Citations
“…It is reported that the yield strength of 3003 at room temperature (RT) after 375°C/24h has been improved to 80 MPa compared with 52MPa after 600°C/24h due to precipitation of dispersoids [7]. Recently, present authors have systematically studied the evolution of dispersoids at relative lower heat treatment temperature (300-425°C) and their influence on elevated-temperature properties in AlMn-Mg 3004 alloys [6,[8][9][10][11][12]. It is found that high volume fraction and well distributed α-Al(MnFe)Si dispersoids are observed after treated at 375°C for 48h, leading to the remarkable improved YS and creep resistance at elevated-temperature.…”
Section: Introductionmentioning
confidence: 99%